Frequency and factors associated with gestational trophoblastic neoplasia in patients treated at a referral center in western Brazil - Ferraz, Raphael Lopes; Gomes, Camilla Soares; Fernandes, Milena Cecília Barroso; Silva, Letícia Soares da; Melo, Monica Maria Bandeira de; Ferreira, Marcio Antônio Couto; Paolino, Bruno Monção; Maestá, Izildinha (Seven Editora, 2024)
Introduction:Gestational Trophoblastic Disease (GTD) is a rare complication in pregnancy that is divided into two groups: the benign form Hydatidiform Mole (MH) and the malignant form Gestational Trophoblastic Neoplasia (GTN). GTN is divided into four types of histopathological disorders, namely: invasive mole (MI), choriocarcinoma, placental site tumor (PTTT) and epithelioid trophoblastic tumor (TTE) Objectives: To identify the frequency of GTN in patients treated at the referral center of the Oncology Control Center Foundation of the State of Amazonas (FCECON) from 2011 to 2018, specifying their sociodemographic data,  clinical data and disease characteristics and mortality. Methodology: This is a retrospective observational study that included patients diagnosed and treated with GTN at FCECON from 2011 to 2018. Data were obtained from medical records, then tabulated and descriptive statistics were performed. Results: The frequency of GTN was 11 patients, aged 29.8 years, most of them brown (72.7%), the most frequent clinical picture was vaginal bleeding (45.4%), IM was the most common form of GTN (54.5%), the low-risk classification was the most frequent (63.6%), the lung was the main site of metastases (54.5%) and mortality was 27.3% of the cases. Conclusion: Despite the advances in diagnosis and treatment described in recent decades, GTN in Amazonas still has a high mortality rate. DOI:https://doi.org/10.56238/sevened2024.007-001